The Transformation of Leadership Forms of Nasdem and Golkar Parties in Increasing Electability in Sidenreng Rappang Regency - Anugrah, Eka; Dema, Herman; Jabbar, Abdul (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
The 2014 and 2019 elections in Sidenreng Rappang Regency marked a significant shift in political dynamics, with the Golkar Party initially dominating and then experiencing a decline in electability, ultimately being replaced by the Nasdem party. This change in political fortunes has sparked interest in understanding the strategies employed by these parties to build and maintain their electability. This research utilizes a qualitative descriptive research method, incorporating data collection techniques such as observation, literature review, and interviews conducted with the assistance of Nvivo 12 Plus data analysis software. Informants were selected through purposive sampling. The findings of this study reveal a clear transformation in the leadership approaches of both the Nasdem and Golkar parties aimed at increasing their electability in Sidenreng Rappang Regency. This transformation is characterized by the adoption of a transformational leadership model. This study delves into the transformation of political party leadership, specifically within the Nasdem and Golkar parties, in the context of enhancing their electability in Sidenreng Rappang Regency. It highlights the shift in leadership strategies from traditional approaches to a more transformational style, which has played a crucial role in influencing the electability of these parties in the region.